Number and Grammatical Gender Attraction in Spanish Pronouns: Evidence for a Syntactic Route to Their Features - Margaret Kandel; Claudia Pañeda; Nasimeh Bahmanian; Mercedes Martinez Bruera; Colin Phillips; Sol Lago (Journal of Cognition)
When a speaker produces a pronoun, they must choose a form that carries the appropriate features. The current study investigates how speakers identify these features. We consider two possible routes: a conceptual-lexical route, whereby pronouns derive their features from the concept of the referent, and a syntactic route, whereby pronoun form is determined through a feature matching operation with the linguistic antecedent. We hypothesize that the use of these two routes should be differentially susceptible to interference from representations other than the pronoun’s referent. We use agreement attraction to distinguish them. In two experiments, we test whether Spanish speakers produce number and grammatical gender attraction errors. We observe small but reliable attraction effects for both features, demonstrating that pronoun formulation can be disrupted by the linguistic representations of nearby nouns. These attraction effects suggest that speakers can use a syntactic route to pronoun form.